Pola Kepemimpinan Kepala Madrasah Aliyah Gani Tirtoasri Tirtomoyo Wonogiri Dalam Meningkatkan Kinerja Guru (Penelitian di MA Gani Tirtoasri Tirtomoyo Wonogiri Tahun Pelajaran 2014/2015) - Shohib Budiono; Muhammad Akhyar; Siti Sutarmi Fadhilah (Universitas Sebelas Maret, 2016)
This study aims at: (1) Acquiring principal leadership pattern executed in MA Gani Tirtoasri Tirtomoyo Wonogiri in the 2014/2015 academic year. (2) Obtaining the efforts being made to improve the performance of teachers in MA Gani Tirtoasri Tirtomoyo Wonogiri in the 2014/2015 academic year. (3) Obtaining the constraints experienced during the principal leadership in the 2014/2015 academic year. (4) Obtaining the results that have been achieved over the principal leadership in the 2014/2015 academic year. This study was conducted in MA GaniTirtoasri Tirtomoyo, MA Gani Tirtoasri have a good school achievement in academic and non-academic. MA Gani Tirtoasri is the oldest Madrasah established in the district of Wonogiri that becomethe establishment embryo of another madrasah. Type of this research is descriptive qualitative research, the research seeks to tell that there is now based on the data, this study also presents the data, analyze, and interpret. The informants are Principals, Madrasah Committee, vice principal of curriculum division, Vice Principals of Infrastructure Division, vice principal of students affairs, Parents, and Students. Data were collected through interviews, observation and documentation. In examining the validity of the data or check the veracity of the data used by extending the duration of the study, the continuous observation, triangulation, either triangulation of data sources and the triangulation of data collection techniques. Data analysis was performed three stages include: data reduction, data presentation and conclusion / verification. The study concluded that: (1) Principal leadership patternapplied in MA Gani Tirtoasri lead to a democratic leadership pattern. (2) Principals has made various efforts to improve teacher performance MA Gani Tirtoasri includes: (a) curriculum development: (b) the development of teaching and learning; (c) human resource development; (d) the development of curricular and extracurricular; (e) the development of links with education stakeholders. (3) The problem faced Principals in the lead MA Gani Tirtoasri in the 2014/2015 academic yearthe main is difficult to change the mindset of teachers becomes a teacher who constantly want to develop in accordance with the demands of the times. (4) The results achieved by the Principals in the lead MA Gani Tirtoasri is achieved various accomplishments championships with both academic and non-academic